SISTEM APRAISAL PADA TEKS IKLAN LAYANAN MASYARAKAT DI KOTA TEBING TINGGI - Rusyda Nazhirah Yunus (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2018)
This research purpose to identify the device Appraisal contained in the text of public service ads in Tebing Tinggi by applying Systemic Functional Linguistic Theory. This research has several objecctives to describe the pattern of Attitude, Engagement and Graduation in the text of public service ads in Tebing Tinggi. The method of the research used in this qualitative techniques referential match . The data used comes from the public service ads board that consists of four pieces with the theme of drugs. The result of the research showed that third of Appraisal devices , Attitude, Engagement, and Graduation . However, the most widely used device is the Graduation . In accordance with the goal of ILM is used to provide information and persuade or encourage people to be better , then the negative appreciation is also found in the text of ILM in Tebing Tinggi.